Suhana Roti Jala / Nur Sufiahana Auladi and Raihana Abd Haris - Auladi, Nur Sufiahana; Abd Haris, Raihana (2023)
Suhana Roti Jala is a partnership owned business by Sufia and Raihana which focuses on making homemade Roti Jala with Chicken Curry and Serawa Durian. The business is located at Kajang, Selangor. Customers can buy through contacting our Facebook page or by contacting on whatsapp. We aim to serve the best quality of food with affordable prices for our customers in Malaysia.